Percutaneous Radiofrequency Ablation of Small (1–2 cm) Hepatocellular Carcinomas Inconspicuous on B-Mode Ultrasonographic Imaging: Usefulness of Combined Fusion Imaging with MRI and Contrast-Enhanced Ultrasonography - Min Woo Lee (Canadian Journal of Gastroenterology and Hepatology, 2018)
Purpose. To assess usefulness of adding contrast-enhanced ultrasonography (CEUS) to fusion imaging (FI) for percutaneous radiofrequency ablation (RFA) of hepatocellular carcinomas (HCCs) inconspicuous on FI alone. Therapeutic outcomes of RFA under CEUS-added FI guidance for HCCs inconspicuous on FI alone were also evaluated. Methods. This prospective study was approved by the institutional review board and informed consent was obtained from all patients. Planning US was performed with FI for 126 patients with a single HCC (1–2 cm) to evaluate the feasibility of RFA by grading lesion conspicuity score using a four-point scale. RFA was performed under CEUS-added FI guidance for HCCs inconspicuous on FI alone. We evaluated how many HCCs initially inconspicuous on FI became conspicuous after adding CEUS. After CEUS-added FI-guided RFA, therapeutic outcomes including rates of technical success, primary technique efficacy, major complications, and local tumor progression were assessed. Results. After adding CEUS, 90.5% (19/21) of all tumors initially inconspicuous on FI became conspicuous, thus enabling direct targeting for RFA. Technical success and primary technique efficacy rates were 94.7% (18/19) and 100% (19/19), respectively. No major complications were observed after RFA. Cumulative local tumor progression rates after RFA were estimated to be 5.3%, 10.8%, and 10.8% at 1, 2, and 3 years, respectively. Conclusion. Adding CEUS to FI is useful for improving the conspicuity of HCCs inconspicuous on FI alone, thus enabling successful percutaneous RFA with excellent therapeutic outcomes.